2022
DOI: 10.3390/cancers14225649
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Somatic Allele Frequency-Adjusted Blood-Based Tumor Mutational Burden Predicts the Efficacy of Immune Checkpoint Inhibitors in Advanced Non-Small Cell Lung Cancer

Abstract: Introduction: Recent studies exhibited the unstable prediction ability of blood-based tumor mutational burden (bTMB) when predicting the response of immune checkpoint inhibitors (ICIs) therapy in patients with non-small cell lung cancer (NSCLC). Circulating tumor DNA (ctDNA) abundance, usually represented by maximum somatic allele frequency (MSAF), was one possible confounding factor influencing bTMB ability in ICIs response prediction. Methods: MSAF-adjusted bTMB (Ma-bTMB) was established and validated in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The predictive efficacy was further validated with the retrospective cohort (OS: HR = 0.20, 95% CI: 0.05-0.84; PFS: HR = 0.30, 95% CI: 0.13-0.70) [57,65]. This biomarker was further validated with the cohorts of the Geneplus Cancer Genome Database and other retrospective cohorts [66].…”
Section: Blood Tmb (Btmb)mentioning
confidence: 99%
“…The predictive efficacy was further validated with the retrospective cohort (OS: HR = 0.20, 95% CI: 0.05-0.84; PFS: HR = 0.30, 95% CI: 0.13-0.70) [57,65]. This biomarker was further validated with the cohorts of the Geneplus Cancer Genome Database and other retrospective cohorts [66].…”
Section: Blood Tmb (Btmb)mentioning
confidence: 99%
“…MSAF considered that those frequencies' participation correspond to the abundance of ctDNA in cfDNA. Unfortunately, MSAF does not consider clonal hematopoiesis; thus, in many cases, TFE is more often recommended [45,46]. On the other hand, Schrock et al observed in NSCLC patients that a lower MSAF level was associated with a higher risk of missing important genomic alterations in the plasma, such as exon 19 deletion and p.Thr790Met substitution in the EGFR gene [47].…”
Section: Cfdna and Ctdna Differentiationmentioning
confidence: 99%